Shopping Malls in Post-war Ontario - Marie-Josée Therrien (Docomomo Journal, 2022)
The development of North American cities and suburbs in the wake of World War II differs from that of European cities, especially if compared to those decimated by bombings where rebuilding dense urban areas, which heavily relied on state intervention, temporarily slowed down suburban growth. Common to both types of cities li1owever, was an unprecedented demand for new housing.